Flexibilidade financeira: estudo comparativo da manutenção de caixa entre empresas brasileiras multinacionais e domésticas negociadas na B3 - Lima, Aparecida de Fátima Alves de (Universidade do Vale do Rio dos Sinos, 2021)
The liquidity storage is an intriguing topic in the scope of corporate finance due to the considerable levels of cash maintained by companies worldwide. Considering that there are singular differences in short-term finances between multinational and domestic companies, and recognizing that macroeconomic conditions can be an important determinant of liquidity storage in companies, was examined the behavior of the cash reserves of Brazilian multinational and domestic companies, traded at B3 between the years 2006 to 2019, with particular interest in the quality of governance, ownership structure and technological intensity. The sample of multinationals was extracted from the FDC's Ranking of Brazilian Multinationals. It was opted for the regression with data in the GMM-Sys panel and the approach proposed by Roodman (2009) in order to observe the influence of the variables of interest on the companies' cash level, avoiding biased estimators resulting from excess of instruments. This article contributes to the cash management literature by multinational companies: The results show that, unlike the case of developed countries like the USA, which for tax reasons started to retain high volumes of cash abroad, multinational companies in Brazil do not retain significantly more cash than domestic firms. At the same time, it presents explanations of the impacts of economic crises on the liquidity storage of the group of Brazilian companies analyzed. It was found that the global financial crisis had a positive impact on companies' cash levels indistinctly, but the Brazilian crisis was significant only for the cash retention of multinational companies.
Keywords: Estocagem de liquidez; Crise financeira; Internacionalização; Liquidity storage; Financial crisis; Internalization; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis